2016
DOI: 10.18632/oncotarget.13698
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-25 targets PKCζ and protects osteoblastic cells from dexamethasone via activating AMPK signaling

Abstract: AMP-activated protein kinase (AMPK) activation could protect osteoblasts from dexamethasone (Dex). This study aims to provoke AMPK activation via microRNA downregulation of its negative regulator protein kinase C ζ (PKCζ). Results show that microRNA-25-5p (miR-25-5p) targets PKCζ's 3’ untranslated regions (UTRs). Forced-expression of miR-25 downregulated PKCζ and activated AMPK in human osteoblastic cells (OB-6 and hFOB1.19 lines), which thereafter protected cells from Dex. Reversely, expression of antagomiR-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Recent studies have proposed protein kinase C ζ (PKCζ) as a negative regulator of AMPK [ 23 , 24 ]. PKCζ was shown to phosphorylate and inactivate the AMPK kinase liver kinase B1 (LKB1), thus shutting down AMPK signaling [ 23 , 24 ]. Reversely, PKCζ silence or inhibition could result in sustained AMPK activation [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have proposed protein kinase C ζ (PKCζ) as a negative regulator of AMPK [ 23 , 24 ]. PKCζ was shown to phosphorylate and inactivate the AMPK kinase liver kinase B1 (LKB1), thus shutting down AMPK signaling [ 23 , 24 ]. Reversely, PKCζ silence or inhibition could result in sustained AMPK activation [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…PKCζ was shown to phosphorylate and inactivate the AMPK kinase liver kinase B1 (LKB1), thus shutting down AMPK signaling [ 23 , 24 ]. Reversely, PKCζ silence or inhibition could result in sustained AMPK activation [ 23 , 24 ]. Here, we show that PKCζ upregulation in human CRC cells silences AMPK to promote cancer cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were expressed as the mean ± SD [ 45 , 57 ]. Comparisons between groups were performed via one-way ANOVA and then Student-Newman-Keuls test (SPSS 18.0).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, AMPK knockdown or mutation abolished this miR-135b-induced cytoprotection against steroid treatment in osteoblastic cells, supporting a critical function of AMPK activation in the actions of miR-135b. Subsequently, they found that miR-25-5p level was increased in patients' necrotic femoral head tissues, targeting and downregulating PKCζ in osteoblastic cells and in turn activating AMPK signaling and protecting cells against the damage induced by steroids [40].…”
Section: Functions Of Mirnas In Preosteoblasts and Osteoblastsmentioning
confidence: 99%